Histidine-rich branched peptides as Cu(II) and Zn(II) chelators with potential therapeutic application in Alzheimer's disease - Lakatos Andrea (DALTON TRANSACTIONS, 2012)
Two histidine-rich branched peptides with one lysine as a branching unit have been designed and synthesized by solid-phase peptide synthesis. Their complex formation with Cu(ii) and Zn(ii) as well as their ability to attenuate the metal-ion induced amyloid aggregation has been characterized. Both peptides can keep Cu(ii) and Zn(ii) in complexed forms at pH 7.4 and can bind two equivalents of metal ions in solutions with excess metal. The stoichiometry, stability and structure of the complexes formed have been determined by pH potentiometry, UV-Vis spectrophotometry, circular dichroism, EPR and NMR spectroscopy and ESI-MS. Both mono- and bimetallic species have been detected over the whole pH range studied. The basic binding mode is either a tridentate {Namino, Namide, Nim} or a histamine-type of coordination which is complemented by the binding of far imidazole or amino groups leading to macrochelate formation. The peptides were able to prevent Cu(ii)-induced A[small beta](1-40) aggregation but could not effectively compete for Zn(ii) in vitro. Our results suggest that branched peptides containing potential metal-binding sites may be suitable metal chelators for reducing the risk of amyloid plaque formation in Alzheimer's disease.